PENGARUH PROFITABILITAS, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP KUALITAS LABA DENGAN GOOD CORPORATE GOVERNANCE (GCG) SEBAGAI PEMODERASI - Nurul Dwi Dhamayanti, 15.05.52.0096; Sunarto, Sunarto (Students' Journal of Accounting and Banking, 2019)
The purpose of this research is to examine and analyze the influence of profitability, capital structure, and liquidity to earnings quality with good corporate governance (GCG) as moderating. The study population was manufacturing companies listed on the Indonesian Stock Exchange (BEI) period of 2013-2017, which amounted to 164 companies. Sampling was done by using purposive sampling method and obtained as many as 43 companies. The analysis technique used is moderated regresion analysis. The results of the analysis can be concluded that : profitability has positive influence with the earning quality. Capital structure has not influence with the earning quality. Liquidity has not influence with the earning quality. Good Corporate Governance weakens the influence of profitability on earning quality.